HUBUNGAN PENGETAHUAN DAN SIKAP SISWI TENTANG KEPUTIHAN DI KELAS IX SMP NEGERI 8 KOTA BINJAI TAHUN 2016 - Helvia Gusvita (Jurnal Riset Hesti Medan, 2016)
Leucorrhoea is a normal thing for women. However, this can turn out to be a dangerous disease due to infection by fungi or viruses, and no less important is the cause of other leucorrhoea, namely bacteria or parasites. This study aims to determine the relationship between student knowledge and attitudes about vaginal discharge using a descriptive study design correlation (correlation study) using a cross sectional study design. The data sources in this study are primary and secondary data using questionnaire and analysis instruments with correlation test and chi-square test techniques using the SPSS program (Statistical Product and Service Solution). The population in this study was female students, to determine the number of samples by taking 30% of the population. Data collection using a questionnaire or questionnaire. From the results of the study showed that the relationship between female knowledge and attitudes about vaginal discharge with a low positive correlation number (positive relationship with weak interpretation) with a level of confidence (α) = 5% = (0.05). For the correlation test obtained the value of P Value = 0.029 (P <0.05), meaning that there is a relationship between student knowledge and attitudes about vaginal discharge. The majority of students have enough knowledge about vaginal discharge as many as 19 people (52.8%). It is recommended that students broaden their knowledge to better understand and understand vaginal discharge.Keywords: Knowledge and attitude, vaginal discharge